2021
DOI: 10.1016/j.brs.2021.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Using cortical non-invasive neuromodulation as a potential preventive treatment in schizophrenia - A review

Abstract: Background: Evidence suggests that schizophrenia constitutes a neurodevelopmental disorder, characterized by a gradual emergence of behavioral and neurobiological abnormalities over time. Therefore, applying early interventions to prevent later manifestation of symptoms is appealing. Objective: This review focuses on the use of cortical neuromodulation in schizophrenia and its potential as a preventive treatment approach. We present clinical and preclinical findings investigating the use of neuromodulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…rTMS could produce a certain intensity of magnetic field by focusing on the brain with a specific shape coil, which makes cortex neuron depolarization or hyperpolarization, and then regulate the excitability of neuron. Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…rTMS could produce a certain intensity of magnetic field by focusing on the brain with a specific shape coil, which makes cortex neuron depolarization or hyperpolarization, and then regulate the excitability of neuron. Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…At PND 21, microglial activation in the mPFC was increased across all Poly I:C groups. The evolution of schizophrenia is found to rely on time-dependent alterations within interconnected brain structures, with alterations in the mPFC suggested as an early sign [55][56][57][58]. It remains to be investigated whether the early increase in microglial activation, specifically within the mPFC, also reflects an early signal of an emerging disorder.…”
Section: Supplementary Treatment Affected the Inflammatory Response I...mentioning
confidence: 99%